Advances in machinery, materials science and engineering application IX proceedings of the 9th International Conference MMSE 2023 - Chen, Min; Giorgetti, Marco; Jin, Bo; Agarwal, Ramesh K. 1947- (IOS Press, 2023)
Intro -- Title Page -- Preface -- About the Conference -- Contents -- Section 1. Mechanical, Material Science and Manufacturing Technology -- The Development of the Cavitated Volume Fraction as a Creep Damage Indicator for Creep Remnant Life Prediction -- Estimation of Composites Delamination due to the Edge Effect -- Mechanical Characterization of AA6061/Clay (Kaolinite) Composites for Industrial Application -- Study on Tensile Strength of High-Density Polyethylene/Polyethylene Terephthalate Blend -- Comparative Studies of V1-xCrxN Films Deposited by Conventional Magnetron Sputtering and Plasma Enhanced Magnetron Sputtering -- Friction Thermal Effect Analysis of High Pressure Turbine Rubbing in Aero-Engine -- Effect of Sc on Microstructure and Corrosion Resistance of Fe-21Cr-4Al Alloy -- A Continuum-Based Degenerated Shell Element and Its Application on the Creep Deformation Analysis of Cladding -- Study on Notched Tensile Properties of 20CrNiMo Steel -- Facile Synthesis and Supercapacitive Properties of PDA/UiO-66 Composites -- Study on Deformed and Solution Treatment Microstructure Evolution of 2219 Alloy -- Analysis of the Thermal Deformation Behaviour of Ti2AlNb-Based Alloys Based on a Modified and Optimised Zerilli-Armstrong Model -- Crack Failure Analysis of Stainless Steel Seamless Pipe -- Research on the Attenuation Mechanism of the Lithium Battery with Computational Chemistry and Surface/Interface Detection Methods -- Study on the Microstructure and Properties of T91 Steel Pipe after 96000 Hours Service Under High Temperature and High Pressure -- The Behavioral Corrosion Characterization of Aluminium AA6061/Chitosan Composites -- Investigation of Microstructure and Residual Stress of Ti-6Al-4V Ultrasonic Assisted Welding Joint -- Study of New Materials for Controlled Grouting Reinforcement.
Open access
Keywords: Konferenzschrift